Stabilizing solar farm power output by micro gas turbine integration: Emission performance - Al-Anati, Abdullah Ibrahim Mahmoud; Mohamad Firdaus, Basrawi; Mohd Hazwan, Yusof; Thamir Khalil, Ibrahim; Amir, Abdul Razak; M. R., R. Chand (IOP Publishing, 2019)
Worldwide growth of Photovoltaics (PV) technology has been close to exponential rate in the past decades. However, the increase of power generation by PV imposes new challenges on the existing electrical grid due to the unpredictability of PV power output that depends mainly on solar irradiance. One of the solutions to stabilize solar farm power output fluctuation by hybridizing Micro Gas Turbines (MGTs) that is controlled to meet the total power production target. Thus, the objective of this paper is to investigate the effect of different operation strategies on the environmental performance on MGT integrated solar farm. Different operation strategies for MGT integrated solar farm have been implemented to constantly produce a total power output of 800 kW throughout the year. The three strategies then compared by analysing emission produced by MGTs. A simulation was conducted in Simulink environment using real ambient temperature and global sun irradiance data. It was found that Operation Strategy 3 reduced carbon dioxide (CO2) by 13.8%, nitrogen oxides (NOx) emission by 3.2%, and carbon monoxide (CO) by 97.9%. This shows that the proposed strategy could stabilize the total power output of the solar farm at minimum emission level.